Skin rash and arthritis a simplified appraisal of less common associations. (24th August 2013) - Cozzi, A.; Doria, A.; Gisondi, P.; Girolomoni, G.
Abstract Skin and joint manifestations are part of the clinical spectrum of many disorders. Well‐known associations include psoriatic arthritis and arthritis associated with autoimmune connective tissue diseases. This review focuses on less common associations where skin lesions can provide easily accessible and valuable diagnostic clues, and directly lead to the specific diagnosis or limit the list of possibilities. This may also affect health care resources as diagnostic tests are often low‐specific, highly expensive and poorly available. This group of diseases can be divided into two subsets, based on the presence/absence of fever, and then further classified according to elementary skin lesions (macular, urticarial, maculo‐papular, vesico‐bullous, pustular, petechial and nodular). In most instances joint involvement occurs as peripheral migrating polyarthritis. Erythematosus macular or urticarial rashes occur in most febrile disorders such as monogenic autoinflammatory syndromes, Schnitzler's syndrome, Still's disease and rheumatic fever and afebrile diseases as urticarial vasculitis. Pustular rash may be observed in chronic recurrent multifocal osteomyelitis (CRMO) and pyogenic arthritis with pyoderma gangrenosum and acne (PAPA) syndrome (both febrile) as well as in Behcet's disease and Synovitis, acne, pustulosis, hyperostosis and osteitis syndrome (both non‐febrile). Papular lesions are typical of secondary syphilis, sarcoidosis, interstitial granulomatous dermatitis, papular petechial of cutaneous small‐vessel vasculitis and nodular lesions of polyarteritis nodosa and multicentric reticulohistiocytosis all of which are afebrile. Differential diagnosis includes infections and drug reactions which may mimic several of these conditions. To biopsy the right skin lesion at the right time it is essential to obtain relevant histological information.